Politik Hukum Pengisian Jabatan Kepala Daerah Dalam Perspektif Demokrasi Dan Otonomi Daerah - Moh Ali Hofi; Cora Elly Noviati (Universitas Moch. Sroedji, 2026)
This study aims to analyze the legal politics of regional head appointment within the perspectives of democracy and regional autonomy in Indonesia. The appointment of regional heads constitutes an essential instrument in local governance, as it directly affects the quality of local democracy and the implementation of regional autonomy principles. In its development, the mechanism for filling regional head positions has not been limited to direct regional elections but has also involved the appointment of acting regional heads under certain circumstances. This policy has generated debates regarding its compatibility with the principles of popular sovereignty and decentralization as guaranteed by the Constitution. This research employs a normative legal research method using statutory, conceptual, and case approaches. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed qualitatively. The findings reveal that the legal politics governing the appointment of regional heads are primarily designed to maintain the stability of local government administration and ensure the continuity of public services. However, the dominant authority of the central government in appointing acting regional heads has the potential to reduce public participation and weaken the essence of local democracy. Therefore, a more democratic and accountable regulatory framework is required while maintaining due consideration for the principles of regional autonomy and the need for effective governance. The reconstruction of the legal politics of regional head appointments should be directed toward achieving a balance between national interests, local democracy, and the strengthening of regional autonomy.